The Unfolded Protein Response in Amelogenesis and Enamel Pathologies - Brookes, Steven J.; Barron, Martin J.; Dixon, Michael J.; Kirkham, Jennifer (Frontiers in Physiology, 2017)
During the secretory phase of their life-cycle, ameloblasts are highly specialized secretory cells whose role is to elaborate an extracellular matrix that ultimately confers both form and function to dental enamel, the most highly mineralized of all mammalian tissues. In common with many other “professional” secretory cells, ameloblasts employ the unfolded protein response (UPR) to help them cope with the large secretory cargo of extracellular matrix proteins transiting their ER (endoplasmic reticulum)/Golgi complex and so minimize ER stress. However, the UPR is a double-edged sword, and, in cases where ER stress is severe and prolonged, the UPR switches from pro-survival to pro-apoptotic mode. The purpose of this review is to consider the role of the ameloblast UPR in the biology and pathology of amelogenesis; specifically in respect of amelogenesis imperfecta (AI) and fluorosis. Some forms of AI appear to correspond to classic proteopathies, where pathological intra-cellular accumulations of protein tip the UPR towards apoptosis. Fluorosis also involves the UPR and, while not of itself a classic proteopathic disease, shares some common elements through the involvement of the UPR. The possibility of therapeutic intervention by pharmacological modulation of the UPR in AI and fluorosis is also discussed.